Metatranscriptional Response of Chemoautotrophic Ifremeria nautilei Endosymbionts to Differing Sulfur Regimes - Seston, Sherry L.; Beinart, Roxanne A.; Sarode, Neha; Shockey, Abigail C.; Ranjan, Piyush; Ganesh, Sangita; Girguis, Peter R.; Stewart, Frank J. (Frontiers in Microbiology, 2016)
Endosymbioses between animals and chemoautotrophic bacteria are ubiquitous at hydrothermal vents. These environments are distinguished by high physico-chemical variability, yet we know little about how these symbioses respond to environmental fluctuations. We therefore examined how the γ-proteobacterial symbionts of the vent snail Ifremeria nautilei respond to changes in sulfur geochemistry. Via shipboard high-pressure incubations, we subjected snails to 105 µM hydrogen sulfide (LS), 350 µM hydrogen sulfide (HS), 300 µM thiosulfate (TS) and seawater without any added inorganic electron donor (ND). While transcript levels of sulfur oxidation genes were largely consistent across treatments, HS and TS treatments stimulated genes for denitrification, nitrogen assimilation, and CO2 fixation, coincident with previously reported enhanced rates of inorganic carbon incorporation and sulfur oxidation in these treatments. Transcripts for genes mediating oxidative damage were enriched in the ND and LS treatments, potentially due to a reduction in O2 scavenging when electron donors were scarce. Oxidative TCA cycle gene transcripts were also more abundant in ND and LS treatments, suggesting that I. nautilei symbionts may be mixotrophic when inorganic electron donors are limiting. These data reveal the extent to which I. nautilei symbionts respond to changes in sulfur concentration and species, and, interpreted alongside coupled biochemical metabolic rates, identify gene targets whose expression patterns may be predictive of holobiont physiology in environmental samples.